2000
DOI: 10.1046/j.1439-0396.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt requirement of beef cattle — feed intake and growth at different levels of cobalt supply

Abstract: Summary In a study using a total of 36 German Simmental beef bulls weighing between 236 kg and about 620 kg the question of what constitutes an adequate Co supply was investigated with reference to the performance criteria growth, feed intake, energy intake, nutrient intake and carcass criteria. The bulls received a diet of corn silage ad libitum and 2.5 kg concentrate for a period of 280 days. Ten rations (R) with graduated Co supplements were fed with mean concentrations of 0.07 (R1), 0.09 (R2), 0.11 (R3), 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
3
37
1
1
Order By: Relevance
“…Cobalt requirements in ruminants are high as absorption is much less efficient than in simple-stomached animals, with about 3% converted to vitamin B 12 , although conversion increases when diet is Codeficient (Smith and Marston, 1970). Andrews (1956) showed that lambs are the most sensitive to Co deficiency under grazing conditions, and Marston (1970) showed that requirements for growing lambs are about 10 times the reported values for adults (also recently confirmed for growing beef cattle: Kirchgessner et al, 1998;Stangl et al, 1999;Schwarz et al, 2000). That way, Co free-choice consumption not only response to diet deficiencies, but also hind:calf consumption ratio observed agree with previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt requirements in ruminants are high as absorption is much less efficient than in simple-stomached animals, with about 3% converted to vitamin B 12 , although conversion increases when diet is Codeficient (Smith and Marston, 1970). Andrews (1956) showed that lambs are the most sensitive to Co deficiency under grazing conditions, and Marston (1970) showed that requirements for growing lambs are about 10 times the reported values for adults (also recently confirmed for growing beef cattle: Kirchgessner et al, 1998;Stangl et al, 1999;Schwarz et al, 2000). That way, Co free-choice consumption not only response to diet deficiencies, but also hind:calf consumption ratio observed agree with previously published data.…”
Section: Discussionmentioning
confidence: 99%
“…A SeMet pode ser transformada a SeCis pela mesma rota que a metionina é convertida a cisteína. Atualmente, a maior parte das recomendações para suplementação de Se para bovinos leiteiros varia entre 0,1 a 0,3mg kg -1 MS, independentemente do estado fisiológico, da idade dos animais ou da forma com que o Se é suplementado (ARC, 1980;GfE, 2001;NRC, 2001 Como o metabolismo dos microminerais nos animais possui um controle homeostático, o organismo regula situações de deficiência, através da mobilização de reservas, e de excesso, através da excreção dos excedentes ou da redução da absorção intestinal (KIRCHGESSNER, 1993;KIRCHGESSNER et al, 1997;SCHWARZ et al, 2000). No entanto, diferente do que ocorre com outros microelementos, parece não existir regulação da absorção intestinal das diferentes formas de Se (VENDELAND et al, 1994).…”
Section: Gierusunclassified
“…raetam contained slightly bigger amounts of cobalt than the other species, but not big enough. Some years ago lower cobalt nutritional values used to be recommended in a number of countries, because cobalt deficiency results in the development of acobaltosis which causes disorders of digestion and metabolism (Schwarz et al 2000).…”
Section: Resultsmentioning
confidence: 99%